Innovation analytics : Tools for competitive advantage - Subramanian, Nachiappan; Ponnambalam, S.G.; Janardhanan, Mukund (London : World Scientific, 2023)
nnovation analytics is an emerging paradigm that integrates information/knowledge, analytics, digital twins and artificial intelligence to support and manage the entire lifecycle of a product and process from inception, through engineering design and manufacture, to service and disposal of manufactured products. Innovation analytics is set to become an integral part of the innovation lifecycle to help make smart, agile decisions and accelerate business growth. Innovation Analytics: Tools for Competitive Advantage provides a comprehensive overview of the challenges and opportunities behind the latest research surrounding technological advances driving innovation analytics; the transition of analytical ideas to interdisciplinary teams; the development of deep synchronicity of skills and production innovation; and the use of innovation analytics in multiple stages of product and process evolution. In exploring the impact of emerging developments in the current climate, researchers and academics will be able to gain insight into real-world usage of analytics for innovation and its contribution toward society. As such, students, scientists, engineers, academics, and management professionals alike will find this title beneficial.
Includes index
Keywords: Tools and Techniques; Data Sources for Innovation; Application Areas; Case Studies; Strategic planning